Anti-Proliferative Activity of Butenyl Isothiocyanate Against Colon Cancer Cell Line (Iraqi Journal of Medical Sciences, 2025)
Background:    Colorectal cancer (CRC) is the third most common malignancy in both men and women. Rectal cancer and colon cancer are frequently considered to be the same condition due to their shared characteristics. Polyps in the colon are the first sign of the disease and can develop into a malignant tumor. Patients with colon cancer often die of tumor recurrence and metastasis. Butyl isothiocyanate belongs to the isothiocyanate family, which has more attention since they have a lot of biological activity. Additionally, acetylsalicylic acid the non-steroidal anti-inflammatory drug significantly lowers the antiproliferative activity of cancer.Objective:    To identify the anti-proliferative activity of butenyl isothiocyanate, acetylsalicylic acid and their combination against colon cancer cell line. In addition to identify the molecular mechanism evaluation of butenyl isothiocyanate by measuring vascular endothelial growth factor (VEGF) gene expression.Methods: Butenyl isothiocyanate and acetylsalicylic acid antiproliferative activity against the CL40 cell line was determined using the (4,5-Dimethylthiazol-2-yl)2,5-diphenyl tetrazolium bromide (MTT) test. Butenyl isothiocyanate gene expression levels were studied quantitatively using real-time polymerase chain reaction.Results: Butenyl isothiocyanate, acetylsalicylic acid, and their combination demonstrated dose-dependent significant suppression of proliferation of the colon cancer cell line CL40 (P <0.001). Furthermore, butenyl isothiocyanate showed a fold diminishing in VEGF gene expression of 35.83 % (P <0.001).Conclusion: Butenyl isothiocyanate, acetylsalicylic acid and their combination exhibited a significant antiproliferative effect. Furthermore, butenyl isothiocyanate\'s molecular mechanism of action was demonstrated to be the down-regulation of VEGF gene expression.Keywords: VEGF, antiproliferation, Butenyl isothiocyanate, Acetylsalicylic acid, MTT, CL-40, colon cancer, gene expressionCitation: Mohamed SJ, Sahib HB. Anti-proliferative activity of butenyl isothiocyanate against colon cancer cell line. Iraqi JMS. 2025; 23(1): 64-74. doi: 10.22578/IJMS.23.1.8